Resource integration through digitalisation: a service ecosystem perspective - Sklyar, Alexey; Kowalkowski, Christian; Sörhammar, David; Tronvoll, Bård (Journal of marketing management, 2019)
As digitalisation increasingly encompasses entire service ecosystems, it modifies resource integration patterns that connect ecosystem actors through strong and weak ties. To clarify how technological development contributes to this change, and how resource integration transforms the service ecosystem, this qualitative case study explores the digitalisation strategy of a market-leading systems integrator in the maritime industry. Based on 40 depth interviews with managers, the findings show how technology increasingly serves as a key operant resource in the transformation of resource integration patterns. The study contributes to ecosystem dynamics research by identifying major differences between the pre-digitalised and digitalised states of a service ecosystem, and demonstrates the dual role of technology in both increasing pattern complexity and facilitating coordination of that complexity.